Bumblebee pollination ensures the stability of both yield and quality of the woody oil crop Paeonia ostii ‘Fengdan’ - Zhang, Kaiyue; Wang, Xiang; Bao, Junyi; He, Xiangnan; Lei, Yang; He, Chunling; Hou, Xiaogai (Basic and applied ecology, 2024)
•The field cultivation of oil tree peony experienced a “medium” pollination deficit.•Excluding pollinator pollination reduced the yield of oil tree peony by 44.24%, and oil tree peony showed a high dependence on bumblebee pollination.•Supplemental bumblebee pollination increased the seed yield of oil tree peony by 82.87% and the oil yield by 10.21%, which reduced the degree of pollination defects to a lower level.•Pollination by bumblebees ensures the stability of yield and quality of oil tree peony over time. Oil tree peony is a unique woody oil crop found exclusively in China. Its seed oil is a highly nutritious edible vegetable oil. However, its seed production varies greatly and is often low. Oil tree peony is a plant that relies on insects for pollination, but inadequate pollination is a common occurrence. In this study, we focused on the Paeonia ostii ‘Fengdan’ species and conducted a five-year study (from 2017 to 2022) in Luoyang, China. Our objective was to assess the extent of pollination deficiency and dependence, as well as quantify the contribution of supplemented bumblebees (Bombus terrestris) to the yield of oil tree peony. We also examined the effect of supplemented bumblebees on the temporal variation in yield through various pollinator survey designs, including supplemented bumblebees (BP), open pollination (OP), pollinator exclusion (EP), self-pollination treatments (SP), and artificial cross-pollination (CP). The results revealed a medium pollination deficit (D = 0.50) at the study sites for three consecutive years from 2020 to 2022, indicating limited pollination for oil tree peony under natural conditions. Importantly, BP significantly compensated for this deficiency (D = 0.22). Over the course of five years, BP increased the yield of oil tree peony by 82.87% on average compared to EP. Furthermore, the yield variation coefficient of EP (CVt=0.20) increased by 100% compared to BP (CVt=0.10). And we also observed significant variability in other yield parameters. Additionally, oil tree peony production was reduced by 44.24% in the absence of flower visitors, and the dependence on BP reached a “high” level. The fatty acid content in the seed oil did not show significant differences across treatments, indicating its stability. Overall, our pollination practices demonstrate that supplementing bee pollination can provide sufficient and stable pollination services, resulting in a higher and more stable yield of oil tree peony seeds.